Analisis Implementasi Pembelajaran Menulis Teks Prosedur Berbasis Pembuatan Video Berteks di SMP Negeri 1 Jeruklegi - Ratino Ratino; Eko Suroso (Lembag, 2025)
The purpose of this study is to analyze the implementation of the practice of writing text procedures based on the creation of texted videos carried out at SMP Negeri 1 Jeruklegi. The background of this research is the low writing skills of students' procedural texts and the need for technology-based contextual learning innovations. This research method is qualitative descriptive with the subject of grade IX students. Data collection was carried out through observation of learning, interviews with students, and analysis of written documents and videos of the procedural texts made. The instruments in the study used observation sheets, interview guidelines, and product assessment rubrics. Data analysis is carried out through several stages such as reduction, presentation, and drawing conclusions. The results of the study show that the implementation of writing practices based on the creation of texted videos is able to increase creativity, student cooperation, and systematic ability in writing. The challenges faced include facilities and infrastructure as well as video production time. Another result obtained is that text-based video writing learning is effective in improving students' digital literacy skills. Teachers play an important role in being facilitators as well as directing in the process of writing to making videos.